CAR-T cells for the treatment of pediatric chronic myeloid leukemia in repeatedly relapsed lymphoid blast phase - Kramp, Laura Jane; Heydrich-Karsten, Christiane; Sembill, Stephanie; Karow, Axel; Lion, Thomas; Chitadze, Guranda; Suttorp, Meinolf; Cario, Gunnar; Metzler, Markus (Annals of Hematology, 2024)
Chronic myeloid leukemia presenting de novo in the blast phase (CML-BP) is a rare diagnosis among pediatric malignancies. We report on a 16-year-old male who presented with CML-BP lymphoid at diagnosis. He was treated with shortened acute lymphoblastic leukemia induction plus the tyrosine kinase inhibitor (TKI) imatinib followed by dasatinib. After achieving molecular remission (MR), hematopoietic stem cell transplantation (HSCT) was performed early after diagnosis. Despite prophylactic dasatinib, he relapsed 3 months later with the kinase domain mutation T315I. Multiple therapeutic approaches including ponatinib, blinatumomab, a 2nd HSCT from a different donor, donor lymphocyte infusions, and high-dose asciminib all resulted in subsequent relapse. Another molecular response was achieved by combining ponatinib plus asciminib with chemotherapy. In this situation, CD19-directed CAR-T cells (Kymriah®) were administered for compassionate use and tolerated without adverse events. Compared to all prior therapies, CAR T-cells maintained remission. After 12 months of follow-up, complete B-cell aplasia and low numbers of CAR-T cells are detectable in the peripheral blood, potentially mediating long-term disease control.
CRIS-Team Scopus Importer:2024-09-27
Keywords: Blast phase; CD19 CAR-T cells; Chronic myeloid leukemia; Refractory leukemia